Proline carrier mutant of Escherichia coli K-12 with altered cation sensitivity of substrate-binding activity: cloning, biochemical characterization, and identification of the mutation. - Ohsawa, M (1988)
Two putP mutants of Escherichia coli K-12 that were defective in proline transport but retained the binding activities of the major proline carrier were isolated (T. Mogi, H. Yamamoto, T. Nakao, I. Yamato, and Y. Anraku, Mol. Gen. Genet. 202:35-41, 1986). One of these mutations and three null-type mutations (K. Motojima, I. Yamato, and Y. Anraku, J. Bacteriol. 136:5-9, 1978) were cloned into a pBR322 putP+ hybrid plasmid (pTMP5) by in vivo recombination. Cytoplasmic membrane vesicles were prepared from the mutant strains and strains harboring pTMP5 putP plasmids, and the properties of the proline-binding reaction of the mutant putP carriers in membranes were examined under nonenergized conditions. The putP19, putP21, and putP22 mutations, which were mapped in the same DNA segment of the putP gene (Mogi et al., Mol. Gen. Genet. 202:35-41, 1986), caused the complete loss of proline carrier activity. The proline carriers encoded by the mutant putP genes, putP9 and putP32, and putP32 in pTMP5-32, which was derived from in vivo recombination with the putP32 mutation, had altered sodium ion and proton dependence of binding affinities for proline and were resistant to N-ethylmaleimide inactivation without changes in the specificities for substrates and alkaline metal cations. The nucleotide sequence of the putP32 lesion located on the 0.35-megadalton RsaI-PvuII fragment in the putP gene in pTMP5-32 was determined; the mutation changed a cytosine at position 1001 to a thymine, causing the alteration of arginine to cysteine at amino acid position 257 in the primary structure of the proline carrier. It was shown that this one point mutation was enough to produce the phenotype of pTMP5-32 by in vitro DNA replacement of the AcyI-PvuII fragment of the wild-type putP gene with the DNA fragment containing the mutated nucleotide sequence.